Glucose Levels and Organoleptic Quality Probiotic Tepache of Pineapple Peel on Variation of Sugar and Fermentation Duration - Sabira, Qurota Ayuni Nuha; Suryani, Titik (Universitas Muhammadiyah Surakarta, 2023)
The probiotic beverage tepache is a variety of natural or processed functional products that contain bioactive compounds with specific physiological functions for health. Pineapple peel is one of the plant base ingredients that can be used as a base for probiotic beverages. The levels of antibacterial compounds, carbohydrates, and sugars in pineapple peel are sufficient to be an essential medium for the growth of Lactic Acid Bacteria (LAB) in probiotic beverages. This research was aimed to determine the glucose levels and organoleptic quality of probiotic beverages tepache of pineapple peel on variation of sugar and fermentation duration. This research used experimental method Completely Randomized Design (CRD) with two-factors, Factor 1 was variation of sugar (G) palm sugar and granulated sugar. Factor 2 was the variation of fermentation duration (F) 3 and 5 days. The results of the research showed that the tepache of pineapple peel had the highest glucose levels in the treatment of G1F1 (palm sugar 100 g with 3-days fermentation duration) at 12,2 %. The best organoleptic quality of tepache pineapple peel was in G2F1 treatment (granulated sugar 100 g with 3-days fermentation duration) with light yellow color, tepache-specific aroma, and sour flavor.